Abductive reasoning and mythic thinking - Campos Vargas, Henry (2018)
This paper shows how abduction is on the base of several examples of mythical thinking. In fact, some times mythical experiences could be explained in different ways, where mythical one appears as a hypothesis that is assumed by a subject or community. So it becomes part of mythical beliefs.